An Incremental Deployment Approach from the Internet to CoLoR - Mengchun Hu; Zhaoxu Wang; Hongbin Luo; Gong Chen (Dianxin kexue)
Focusing on poor configurability, user-unfriendliness, exclusivity, difficulty in supporting large scale deployment of new network architectures, an approach in incrementally deploying the CoLoR future internet architecture was proposed. In particular, the research background, the design principles, the main components of the mechanism and specific solutions under a variety of scenarios were described.